Absorption of resonance laser radiation in ultracold plasma. (September 2017) - Shaparev, N.Ya.
Abstract: The absorption of resonance laser radiation in an expanding ultracold plasma is considered. Initially the optical thickness τ 0 of the medium decreases due to correlation heating of the ions; the subsequent lowering of τ 0 is due to the variation of radial ion velocities. The expanding optically thick medium is shown to become transparent when the ratio between the particle expansion velocity at the sphere boundary and the thermal velocity exceeds the optical thickness τ 0 .